Monitoring sleep in elite athletes and interventions to enhance sleep - Halson, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Sleep is considered the best recovery strategy available to athletes and has important roles in physical and mental performance, illness and injury prevention, mood, metabolism and cognitive function. Research has established that athletes face numerous sleep challenges and have reduced sleep quality and quantity when compared to the general population. Alongside the rapid increase in research in sleep and athletes is the proliferation of wearable devices to assess sleep. The latest scientific knowledge regarding sleep measurement tools will be provided, including validation research, specific metrics provided by wearables which have sufficient validity and relevance to athletes, and availability, security and access to data. Important caveats for consideration when using these devices with athletes will be presented. Further, is important to understand how to appropriately use metrics derived from wearables and activity monitors to improve sleep. Feedback and behaviour change strategies form essential components of athlete monitoring and education, with scientific evidence developing in this area. Other strategies to increase sleep in athletes, including nutritional and psychological strategies will be outlined.